Iot cloud simulation managing resources: an overview - Hamza, Nidal Abdelgadir Ahmed; Mazlina, Abdul Majid; Abdulgabber, Mansoor Abdullateef (Universiti Malaysia Pahang, 2018)
This paper is an overview of the cloud management resources for the Internet of Things data. The IoT model is facilitating the development of our stream environment towards improved services especially in areas such as home appliances, smart grid, automated environmental pollution control and healthcare among others. It is well known that these applications often generate huge amount of data which makes necessitates the need for storage and analysis. However, data aggregation and scheduling are still some of the major challenges for cloud infrastructure to attain minimized latency with maximized throughput. This paper aims to present the prospective role of simulation resource management in IoT Cloud. Hence the Objective of the paper is to discuss the issues and challenges to resource management for data aggregation and scheduling resources by reviewing the literature. This search identified 33 reviewed studies in resource management domain. Based on the result gathered, 18 studies have been highlighted with respect to data aggregation and scheduling. This paper provides useful comparison for technique of data aggregation and scheduling.